Enforcement of the Police Professional Code of Ethics for Members of the National Police Perpetrators of Sexual Violence Against Children - La Jagole; Hadibah Zachra Wadjo; Astuti Nur Fadillah; Judy Marria Saimima (LUTUR Law Journal, 2026)
This article analyzes the mechanism for enforcing the National Police's professional code of ethics against members who are proven to have committed sexual violence against children in the jurisdiction of the Maluku Police. The purpose of this study is to find out and examine the effectiveness of the ethics enforcement mechanism and identify inhibiting factors in its implementation. This study uses empirical juridical law research methods with a focus on normative approaches such as statute approach and conceptual approach. Data collection was carried out through document studies and interviews with the Maluku Police Internal Affairs Division and related units. The findings of the study show that the ethics enforcement mechanism regulated in Police Regulation Number 7 of 2022 is empirically still sub-optimal, characterized by the postponement of ethics hearings until a criminal verdict has permanent legal force. The main inhibiting factors include the lack of Propam personnel, dependence on criminal processes, an unintegrated reporting system, and an organizational culture that is resistant to transparent and firm enforcement. This shows the inequality between regulation and the reality of implementation, which demands a thorough internal reform to restore institutional integrity.